Rilke’s Modernist Vision School: from a Diary to a Diary Novel (Proceedings of Southern Federal University. Philology, 2016)
Vera V. Kotelevskaya (Southern Federal University, Rostov-on-Don, Russian Federation)Rilke’s novel «The Notebooks of Malte Laurids Brigge» and his early diaries provide basis for the genre analysis of a modernist subject’s selfpresentation. Similarities and differences between personal and fictitious diaries are examined within the context of visuality. Rilke’s visual method is compared with Joyce’s «epiphany», «the involuntary memory» of Proust, and expressionist grotesque. Development of a clear vision of things and oneself therein is a motive explored by Rilke in his diaries from periods of intense engagement with the visual arts and the landscape: «Florentine Diary» (1898) and «Worpswede Diary» (1900). The diary is considered the most authentic written form for modernist subjects characterized by their «longing for oneself», alienation from their environment, nonfinality, and linguistic skepticism. Rilke’s «Florentine Diary» is akin to the traditional travelogues of the 18th and early 19th centuries while «Worpswede Diary» may be regarded as a preview of sorts for «The Notebooks of Malte Laurids Brigge». As in the novel, the narrator encounters the reader in medias res. The text contains much implicit information given the writer’s hermetic condition, overwhelmed by the otherness of the landscape. Thus, the ideas of life as art and vision as a tool of subjective exploration and appropriation of landscape are realized in Rilke’s early diaries.Key words: diary, diary novel, modernism, Austrian literature, RilkeDOI: 10.18522/1995-0640-2016-4-35-40